Identificar los peligros y evaluar los riesgos en los grifos flotantes del Puerto de Productores - Iquitos. Loreto – perú. 2022 - Vargas Tamayo, Rosita (2023)
In the river port of producers, located on the Itaya river, a study was carried out to identify the dangers and determine the risks to which workers are exposed in the facilities of the floating taps of the producer port, where it was determined that in the different floating faucets from the port of producers who are dedicated to the supply and sale of fuels in the itaya river I have been able to identify that the most frequent hazards are mostly hazards from the work environment or locations with a moderate level of risk and the chemical hazards that They are presented with a significant level of risk, among Chemical hazards we have exposure to gases and fuel odors depending on the duration, exposure, concentration, the type of chemical substances involved such as gasoline, diesel and other petroleum products These can have several effects on health, since they are potentially dangerous to human health. These activities carried out by floating faucets are similar in terms of conditions, space, equipment implementation, which is why it is stated that the main dangers that could be generating accidents and occupational diseases in workers are chemical hazards with a significant level of risk and at a moderate level of risk the hazards of the work environment or location.